Gender differences in pursuing leadership positions in the Netherlands; a study in cardiovascular PhD candidates. (25th November 2020) - Kessler, E.L; Goversen, B; Derks, B; Den Ruijter, H.M
Abstract: Background: Gender studies demonstrate that more balance in gender within research teams improves performance and output. In the Netherlands, (bio)medical master programs currently enroll more women than men, but scientific leadership positions are still mainly occupied by men. Women tend to refrain from academic careers – referred to as the "leaking pipeline phenomenon" – and reasons are e.g. family planning or glass-ceiling. Women start working part-time even before family planning comes into play. Moreover, more agentic character traits are associated with the male gender and success than communal traits, which are more associated with the female gender. Purpose: To be able to promote academic careers amongst women, we have to know their intrinsic motivation and adapt the initiatives accordingly. Therefore, we created a questionnaire to evaluate the intrinsic motivation of (bio)medical PhD candidates on pursuing a leadership position. Methods: In this study, 143 PhD candidates (68% female) of Dutch cardiovascular research programs participated in an online questionnaire, which was not mentioned to be used for gender studies. Results: Our data shows that less female cardiovascular PhD candidates in the Netherlands aim at or can imagine having a leadership position – defined as full professor, dean, corporate executive officer, (medical) group leader etc. – in the future compared to male candidates (29% female versus 46% male and 40% female versus 63% male, respectively). In men, this decision seemed to be less influenced by their wish to have children, but both men and women would like to be able to work part-time in the future. When asked whether a certain initiative would positively influence their decision to pursue a leadership position, women reported that position certainty and alternative measures of impact would motivate them to pursue leadership positions rather than gender-specific initiatives. Men, in turn, would be motivated by an adequate mentor, which seems to lack in the current system (40%). Free day care for children would persuade 67% of women and 43% of men and possibilities for a part-time position would persuade 73% of women and 59% of men to pursue a leadership position. When asked, which of their own character traits would benefit or hamper someone in a leadership position, agentic traits were seen as more beneficial for a leadership position, but also more hampering in both genders. Conclusion: Less female cardiovascular PhD candidates in the Netherlands aim at or can imagine having a leadership position compared to male candidates. However, women reported that position certainty and alternatives to the impact factor would motivate them to pursue a leadership position. Possible part-time work would persuade both genders in pursuing a leadership position. Additionally, agentic character traits are seen as beneficial for a leadership position amongst these candidates, but simultaneously thought to be hampering. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): University Medical Center Utrecht